The Global Crisis and the Impact on Remittances to Developing Asia. - Jha, S; Sugiyarto, G; Vargas-Silva, C (Taylor and Francis, 2010)
Remittances to Asia plunged during the 1997 Asian financial crisis, but the drop was temporary as the flows were increasing once again after just one year. The current crisis, however, is fundamentally different in that even the main remittance-sending countries have been adversely affected. The global nature of this crisis raises several questions such as whether the remittances slowdown will also last for a short time or developing Asia should prepare for a long period of remittance stagnation. This study examines remittances data of several Asian countries to shed light on such questions. The results suggest that while remittance flows to key recipients in the region have slowed down, there has not been a sharp drop. Furthermore, there is no indication that the remittance flows will slow down further, suggesting that the flows should be back on a higher growth path in a few years. It is unlikely, however, to see the same growth rates of the past, given that an important share of that growth during the last two decades was due to better recording of remittances and an increased use of wire transfers on the part of migrants. The study also provides policy options to deal with the future outlook of remittances.